Proposed production process improvement with a lean manufacturing approach on the electrolytic tinning line - Evi Febianti; Ade Irman S Mutaqin; Firdha Tamia Puteri; Shanti Kirana Anggraeni; Nuraida Wahyuni; Ratna Ekawati; Ani Umyati (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
Industry competition is currently getting tighter; companies must produce quality products, deliver on time, and provide the best service to consumers. It can be real realized minirealisedaste that occurs in the production process to achieve this. In this study, lean manufacturing will be applied to minimize waste by describing the entire production process through Value Stream Mapping, identifying the most dominant waste using the Waste Assessment Model (WAM) method, and selecting VALSAT tools based on final weights. WAM, identification of causes using Fishbone diagrams, and suggestions for improvement using 5 Whys Analysis. The results show that waste is dominant, namely waste defect with a percentage of 21.66% and waste inventory of 20.34%. Proposed improvements made to reduce waste defects a traditional singing the contaminant inspection method, conducting regular inspections, and cleaning machine parts, changing the coating thickness gradually, providing training to operators regarding the handling of the process section, and adding a thermometer near the steam supply. Meanwhile, to reduce inventory waste, namely by including the storage date limit on the Tin Mill Black Plate (TMBP) raw material, rearranging the TMBP storage area, conducting periodic TMBP inspections, and providing training and direction to operators regarding the TMBP transfer process.